Whole scrapings of cassava root in diets for broilers from 1 to 21 days of age - Ferreira, Antônio Hosmylton Carvalho; Lopes, João Batista; Abreu, Márvio Lobão Teixeira de; Santana Júnior, Hermógenes Almeida de; Araújo, Fernando Silva; Saraiva, Alysson (Acta Scientiarum. Animal Sciences, 2014)
The study was conducted to evaluate the effect of including whole cassava root scrapings (WCS) in diets of broilers on performance and the metabolizability of dry matter, crude protein, and gross energy and on nitrogenous balance. Four hundred female and 100 male broilers from Ross strain were used in the performance and metabolism studies, respectively. In both studies, broilers were allotted in completely randomized block design with five treatments and four replicates. The experimental unit was represented for twenty birds per box for performance study and five birds per metabolic cage for metabolism study. The treatments consisted of diets containing 0, 5, 10, 15, and 20% WCS inclusion. Up to 5.1% WCS can be included in the diet of broilers from 1 to 21 without compromising feed conversion and productive efficiency index. Dry matter, crude protein, and gross energy metabolizability and the nitrogen balance of the diets are not influenced by the inclusion of whole cassava root scrapings up to 20% in diets of broilers from 1 to 21 days of age.